Revenue Recognition in Financial Statements: An Introduction - Kashyap (V R P) Ed.; Mrudula (E) Ed. ("52, Nagarjuna Hills,Hyderabad - 500 082", 2005)
Financial Statements
50
Keywords: Financial Statements